Spatio-temporal temperature and precipitation patterns in the southern Peruvian Andes - insights from the Climandes project - Spirig, C. (2020)
In the southern Peruvian Andes, climatic threats such as water scarcity or frost pose major challenges for agriculture. Such events may result in severe yield losses threatening the livelihood of smallholder farmers due to missing adaptive and coping strategies. Knowledge on climate variability and change, on the current state of the climate, as well as short- to midrange predictions potentially improve the farmers’ risk management. However, such knowledge is only partly available and often does not reach rural communities. Climandes, a pilot project of the Global Framework for Climate Services, tackled these shortcomings through the enhancement of climatological observations, the production of gridded datasets using satellite and station observations, the verification of seasonal forecasts to determine their usefulness for small-scale applications, and through the establishment of communication channels and user engagement. This contribution highlights some of the insights from the Climandes project: climatological analyses of spatio-temporal patterns in the southern Peruvian Andes, past trends, as well as the performance of seasonal forecasts in the region. The work focuses on temperature and precipitation using the newly developed gridded datasets, quality controlled observational data, and seasonal forecasts of ECMWF SEAS5.